Vitamin C partially attenuates male reproductive deficits in hyperglycemic rats - Damasceno Débora C; Campos Kleber E; Fernandez Carla DB; Fernandes Glaura SA; Anselmo-Franci Janete A; Kempinas Wilma DG (BMC, 2011)
Abstract Background Hyperglycemia can impair the male reproductive system in experimental animals and in men during reproductive age. Studies have shown that vitamin C has some good effects on male reproductive system, and therefore vitamin C treatment could attenuate the dysfunctions in this system caused by hyperglycemia. Thus, the objective of this work was to evaluate whether vitamin C treatment could attenuate reproductive dysfunctions in hyperglycemic male rats. Methods Adult male rats were divided into 3 groups: a normoglycemic (n = 10) and two hyperglycemic (that received a single dose of streptozotocin - 40 mg/kg BW). The two last groups (n = 10 per group) were divided into: hyperglycemic control (Hy) and hyperglycemic + 150 mg of vitamin C (HyC), by gavage during 30 consecutive days. The normoglycemic and hyperglycemic control groups received the vehicle (water). The first day after the treatment, the rats were anesthetized and killed to evaluate oxidative stress biomarkers (TBARS, SOD, GSHt and GSH-Px) in the erythrocytes, body and reproductive organ weights, sperm parameters, plasma hormone levels (FSH, LH and testosterone), testicular and epididymal histo-morphometry and histopathology. Results Compared with the normoglycemic animals, hyperglycemic control rats showed reduced weight of the body and reproductive organ but testis weight was maintained. It was also observed reduction of testosterone and LH levels, seminiferous tubular diameter, sperm motility and sperm counts in the epididymis. In addition, there was an increase in morphological abnormalities on spermatozoa as well as in oxidative stress level. Vitamin C reduced the oxidative stress level, diminished the number of abnormal sperm, and increased testosterone and LH levels and seminiferous tubular diameter but did not show improvement of sperm motility in relation to the hyperglycemic control group. Hyperglycemia caused a rearrangement in the epididymal tissue components (stroma, ephitelium and lumen) as demonstrated by the stereological analysis results. However, this alteration was partially prevented by vitamin C treatment. Conclusions We conclude that vitamin C partially attenuated some male reproductive system dysfunctions in hyperglycemic rats.